Dryland Cane Hay in Western Kansas (W-CH-F) Rotation - O'Brien, Daniel M.; Sartwelle III, James D. (My University, 1995)
This publication estimates the costs and returns associated with a typical sorghum sudangrass hybrid planted at heavier seeding rates and harvested as a hay crop in western Kansas.
MF997_1995_10
Keywords: MF997; Economics; Crops; MF